(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2020)
The paper is divided in three sections, all linked by the common topic revolving around the Piazza Fontana massacre, its memory and the historiography related to it. The first section presents the most recent debate’s topics, fifty years to the day after the massacre; the second section offers a memoire of Corrado Stajano, since then a protagonist of the Italian intellectual and civil life; the last section aims at presenting an overview of what historians have written about the sensitive topic of US role in the so-called strategy of tension that invested Italy ever since Piazza Fontana.